Agnes Grey - Brontë, Anne, 1820-1849 (Modern Library classics., 2003)
Anne Bronte's 'Agnes Grey' tells the story of a young woman forced by circumstances to take on the role of governess in an aristocratic Victorian household, and how this stressful and at times humiliating role shapes her youthful character. The book is seen by many as a barely-disguised critique of Victorian morality, especially that society's hypocritical stance on women's enforced domesticity, marriage and the bringing up of children. --Publisher.